Isolation and Identification of Biofilm-Forming Staphylococcus Aureus in Commercial Cow Milk Products - Yambise, Dominggas; Ariestanti, Catarina Aprilia; Budiarso, Tri Yahya (SCISCITATIO, 2020)
Food poisoning caused by the contamination from Staphylococcus aureus are frequently found in foodespecially in dairy products. Pasteurization process in milk production was not enough to kill S. aureus becauseit formed biofilm that could survive in high temperature. This research aimed to study the presence of biofilmforming S. aureus in samples from packed commercial milk products in Yogyakarta City, Indonesia. Twentyisolates from dairy products were grown in Brain Heart Infusion (BHI) broth then inoculated into Braid-ParkerAgar (BPA) medium to get the candidate of S. aureus isolates. These isolate candidates were selected usingMannitol Salt Agar (MSA) and Congo Red Agar (CRA) medium. Another selection was done by carbohydratefermentation analysis and confirmed using API STAPH. Confirmation analysis showed that eight isolateswere identified as S. aureus. Another two isolates were identified as S. xylosus and S. haemolyticus. Therefore,it indicated the presence of Staphylococcus aureus as contaminant in dairy products.